The mark of the promenade architecturale and the trivalent nature of urban space. The case of Buenos Aires, Argentina - Regalado, Gerardo (2023)
The recovery of socially and environmentally degraded urban fabrics through land management instruments implies the recycling of former city structures and the proposal of a new, modern, contemporary and global fabric. This is the case of the Puerto Madero project in Buenos Aires, Argentina. This determines an evolution in the way of thinking, feeling and acting of the urbanite, since it develops the route through the urban space in a Le Corbuserian sense (promenade architecturale). In this way, the urban fabric is appreciated from a trialectical interpretation of its historical nature, in space and time, whose transformation has occurred in a physical, social and symbolic way